Comparative Outcome of Short Term Versus Long Term Catheterization after Vaginal Hysterectomy - Akther, Shamima; Siddiqua, Shamima; Sultana, Nargis; Mabud, Farah Naz; Hossen, Md Abul; Waddader, Priyanka (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Urinary catheterization after vaginal hysterectomy is commonly performed to evaluate urine output and to avoid urinary retention. The aim of this study was to determine the advantages of short term catheterization in comparison to long term catheterization after vaginal hysterectomy due to uterovaginal prolapse. Materials and methods: This randomized clinical study was conducted for 1 year (July 2014- July 2015) in the Department of Obstetrics and Gynecology, Chittagong Medical College Hospital (CMCH) on 100 women with 20 utero vaginal prolapse underwent vaginal hysterectomy. After selection and randomization women who had under gone vaginal hysterectomy were grouped two. Urinary catheter was removed after 24 hours in group A and after 72 hours in group B. Observations were recorded and statistical analysis performed. Results: Study showed that duration of catheter did not affect the duration of first voiding time after removal of catheter (RR=.934). 6% of women in group A and 2% women in group B had residual volume of urine >200 ml but residual volume of urine was significantly higher in group B (RR=0.714). Re-catheterization needed 6% patients in group A and 2% in group B (RR= 3.000). Urinary Tract Infection (UTI) was significantly higher 14% versus 2% in group B than group A (RR= 0.143). Mean duration of hospital stay after operation was 2.58 days in group A and 4.16 days in group B (RR= 0.480). Conclusion: Short term catheterization is more beneficial than long term catheterization. Because it results in low incidence of urinary tract infection, less patient discomfort and reduces the mean hospital stay. JCMCTA 2021 ; 32 (1) : 83-88